Aspectos computacionais na geometria da espiral de Teodoro - Gonçalves Junior, Eduardo Manuel (2015)
The present work is a study of Teodoro spiral, for the geometric aspects of the curve. At rst, the construction of Teodoro spiral in two and three dimensions is made. And through the softwares, GeoGebra and wxMaxima were developed respectively, the geometric constructions and the necessary calculations. With the possession of the spiral of concatenation, observe the pattern of behavior of growth and position, the collared peccary in the n - th triangle. Going through measurements of Teodoro spiral with other spirals such as the Archimedean, we come to denote behavior patterns in expanding spiral. The following is an arithmetic study on the spiral obtained by the length of the branches of the same, both perfect and imperfect hits with square also spaced apart relationship between them allows us to observe numbers as the . The distribution of prime numbers is seen as the nal part of this study, where you see speculatively allowing the formation of new curves on the spiral, as parabolas.